Literatur Review MSDM : Pengaruh Kepemimpinan, Kompensasi, dan Lingkungan Kerja Terhadap Kepuasan Kerja Karyawan - Jajang Roni Aunul Kholik; Shavira Sri Rahayu; Adelina Suryati; Zaharuddin (Jurnal Akuntansi, Bisnis dan Ekonomi Indonesia (JABEI), 2024)
Job satisfaction is a very important aspect to pay attention to in the world of work. Job satisfaction is one of the key factors in work productivity, retention and employee welfare in the work environment. In order to understand and improve job satisfaction, it is important to identify the factors that influence job satisfaction. This research was conducted to determine the influence of leadership, compensation and work environment on employee job satisfaction. This research method was carried out using a descriptive analysis approach using qualitative methods and literature study by examining theories in books and online journals. The research results show that the leadership, compensation and work environment variables as a whole have a good role and have a positive effect on employee job satisfaction. Good leadership, empathy, communicative and participative, providing bonuses/incentives for achieving company targets, providing conducive facilities and work spaces and a safe and comfortable atmosphere should be implemented by companies to increase employee job satisfaction.